THE ART OF CONNECTING CULTURES (Religious dialogue and cooperation, 2024)
Four major ‘ideal type’ models may be distinguished in cultural relations in society:Monocultural (monopoly of one culture), Multicultural (living apart together, in mutual tolerance),Secular (rule of law, equality, culturally neutral) and Intercultural (different cultures connected inequivalence). Cultural diversity will become more prominent in the wake of increasing globalisationand migration – which makes the challenge of connecting cultures more urgent than ever.This essay reports on a content analysis of the proceedings of two European conferences on religiousdialogue and cooperation (2019, 2022) in Struga, North-Macedonia. These suggest thattoday cultures are being disconnected rather than connected. Where several major cultures co-existthey struggle for cultural priority; where one dominant culture exists it defends itself againstintrusion by other cultures. At the same time there is a persistent pull towards the secular model.This stands in the way of coming closer to the intercultural model. Movement in the direction of anintercultural model appears to remain restricted to statements of political and religious correctnessor incidental grass roots initiatives.This essay will offer a survey of policies that have had a positive and negative effect onconnecting cultures, leading to explore the transition to an intercultural society. The criticalvariables in that process will be identified and analysed, leading to proposals for proactivepolicies to strengthen the connecting process.
Keywords: cultural diversity; religion; secular modernity; pro-active policy